TiO2 supported on reed straw biochar as an adsorptive and photocatalytic composite for the efficient degradation of sulfamethoxazole in aqueous matrices. (October 2017) - Zhang, Hanyu; Wang, Zhaowei; Li, Ruining; Guo, Jialei; Li, Yan; Zhu, Junmin; Xie, Xiaoyun
Abstract: Heterogeneous photocatalysis namely titanium dioxide supported on reed straw biochar (acid pre-treated) (TiO2 /pBC) was synthesized by sol-gel method. The morphology, surface area and structure of TiO2 /pBC were characterized by scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET), and X-ray diffraction (XRD). Low calcination condition maintained the structure of biochar completely and prevented the agglomeration of TiO2 particles. Due to the combination of adsorption and photocatalysis, TiO2 /pBC performed higher removal efficiency of sulfamethoxazole (SMX) than pure TiO2 powder under UV light irradiation. The photocatalytic degradation (PCD) of SMX was also studied with the water collected from the Yellow River. Three high concentration inorganic anions (Cl −, NO3 −, SO4 2− ) of the river exerted certain degree of detrimental effects on the contaminant degradation. TiO2 /pBC showed stable photocatalytic activity after five sequential PCD cycles. The biochar was able to promote further PCD on TiO2 by adsorbing SMX and intermediates thereby prolonging the separation lifetime of electrons (e − ) and valence band hole (h + ). The transformation intermediates of SMX were identified and three possible degradation reactions of hydroxylation, opening of isoxazole ring and cleavage of SN bond might occur during the PCD of SMX. Graphical abstract: Highlights: TiO2 /pBC as a new environmental-friendly photocatalyst was synthesized. The TiO2 /pBC showed higher mineralization of sulfamethoxazole than pure TiO2 . Common anions which exist in the Yellow River inhibited the photocatalytic process. The photocatalytic activity of TiO2 /pBC was stable over many regeneration cycles. Four degradation pathways of sulfamethoxazole by TiO2 /pBC were proposed.